Copper metabolism and its role in diabetic complications: A review - Dongkai Jia; Lulu Liu; Wei Liu; Jinjie Li; Xin Jiang; Ying Xin (Elsevier, 2024)
Disturbances in copper (Cu) homeostasis have been observed in diabetes and associated complications. Cu is an essential micronutrient that plays important roles in various fundamental biological processes. For example, diabetic cardiomyopathy is associated with elevated levels of Cu in the serum and tissues. Therefore, targeting Cu may be a novel treatment strategy for diabetic complications. This review provides an overview of physiological Cu metabolism and homeostasis, followed by a discussion of Cu metabolism disorders observed during the occurrence and progression of diabetic complications. Finally, we discuss the recent therapeutic advances in the use of Cu coordination complexes as treatments for diabetic complications and their potential mechanisms of action. This review contributes to a complete understanding of the role of Cu in diabetic complications and demonstrates the broad application prospects of Cu-coordinated compounds as potential therapeutic agents.